Julia Kristeva Intertextual of Feminism in the Film Pangku by Reza Rahardian - Agung Drajat (Bayani, 2026)
Reza Rahadian's film Pangku represents the lives of women who are under social, economic and patriarchal cultural pressure. Through the main character, Sartika, this film shows how women must face various life constraints while fulfilling their roles as mothers and breadwinners. This study analyzes the film "Pangku" as a site of feminist discourse within Indonesian cinema. Employing Julia Kristeva's theory of intertextuality and semanalysis, the research examines how the film absorbs and transforms cultural narratives of female labor. The analysis reveals a dialectic between the patriarchal symbolic order and eruptions of the semiotic, manifested through the protagonist's corporeal resistance. The protagonist, analyzed as a "subject-in-process," locates agency in subtle disruptions, offering a complex feminist critique of systemic oppression rather than a simple narrative of liberation. The researcher's findings show that five main frames occur, namely first, the existence of an Intertextual dialogue: "Pangku" and the Sociocultural Narrative of Indonesian Womanhood, second, the existence of Patriarchal Ideology in the Narrative and Dialogue of "Pangku", third, the Emergence of Semiotic Eruptions in Body Expressions and Affective Disorders that Challenge Dominant Meanings, fourth, Navigating Agency and Resistance in the Trajectory of Female Protagonists, and finally, the need for Negotiation of Subversion and Rewriting of "Pangku" in Indonesian Cinema